Investigating knowledge management: can KM really change organisational culture?. Issue 1 (8th February 2016) - Corfield, Alison; Paton, Rob
Abstract : Purpose: – The purpose of this paper is to investigate the relationship of knowledge management (KM) with organisational culture, a subject of interest to academics and KM practitioners. Design/methodology/approach: – It is based on case study research in the voluntary sector, which is relatively less studied than the commercial or public sectors. Findings: – One major finding was that although culture was recognised as an intricate concept, KM programmes were often simplistically intended to "change culture". Two instances of long-term change were identified. Strong and persistent leadership, with a clear rationale for culture change, and also a well-established technology innovation programme, using local "champions" to help align knowledge programmes with daily work routines, did have an impact on organisational culture. Research limitations/implications: – The findings provide food for thought for practitioners in the voluntary sector. As external pressures and common technology are leading the different sectors to follow more similar work practices, it is likely that the findings of this paper will have relevance also for other sectors, where organisations face similar resource constraints. Practical implications: – The paper provides a thoughtful analysis of data collected over several years that suggests sectoral differences will not be the crucial factor to consider when looking at the impact of KM. Originality/value: – It provides practical examples of what has worked to "change organisational culture" and what has not, as well as ideas for future research.